To simplify the expression 1/2(x + 4) + 1/4(4x - 2), we'll first distribute the 1/2 and 1/4 across the parentheses.
1/2(x + 4) + 1/4(4x - 2) = (1/2 * x + 1/2 * 4) + (1/4 * 4x - 1/4 * 2)
Simplifying further,
= 1/2x + 2/2 + 4/4x - 2/4
= 1/2x + 1 + x - 1/2
= (1/2x + x) + (1 - 1/2)
= (3/2x) + (1/2)
So, the simplified form of 1/2(x + 4) + 1/4(4x - 2) is (3/2x) + (1/2).
Add: 1/2(x+4)+1/4(4x−2) .
5 answers
wrong
I apologize for the mistake.
To simplify the expression 1/2(x + 4) + 1/4(4x - 2), we'll first distribute the fractions across the parentheses.
1/2(x + 4) + 1/4(4x - 2) = 1/2 * x + 1/2 * 4 + 1/4 * 4x - 1/4 * 2
Simplifying further,
= 1/2x + 2/2 + 4/4x - 1/2
= 1/2x + 1 + x - 1/2
Combine like terms,
= (1/2x + x) + (1 - 1/2)
= (3/2x) + (1/2)
So, the simplified form of 1/2(x + 4) + 1/4(4x - 2) is (3/2x) + (1/2).
To simplify the expression 1/2(x + 4) + 1/4(4x - 2), we'll first distribute the fractions across the parentheses.
1/2(x + 4) + 1/4(4x - 2) = 1/2 * x + 1/2 * 4 + 1/4 * 4x - 1/4 * 2
Simplifying further,
= 1/2x + 2/2 + 4/4x - 1/2
= 1/2x + 1 + x - 1/2
Combine like terms,
= (1/2x + x) + (1 - 1/2)
= (3/2x) + (1/2)
So, the simplified form of 1/2(x + 4) + 1/4(4x - 2) is (3/2x) + (1/2).
still wrong
I apologize for the persistent errors. Let's try solving the expression correctly:
To simplify 1/2(x + 4) + 1/4(4x - 2), we'll begin by distributing the fractions across the parentheses:
1/2(x + 4) + 1/4(4x - 2) = 1/2 * x + 1/2 * 4 + 1/4 * 4x - 1/4 * 2
= (1/2)x + 2/2 + (1/4)(4x) - (1/4)(2)
= (1/2)x + 1 + (1/4)(4x) - (1/4)(2)
= (1/2)x + 1 + (1/4)(4x) - 1/2
Next, we'll simplify each fractional coefficient:
= (1/2)x + 1 + (4/4)(x) - 1/2
= (1/2)x + 1 + (x) - 1/2
Combining like terms:
= (1/2)x + x + 1 - 1/2
= (1/2 + 2/2)x + 2/2 - 1/2
= (3/2)x + 1/2
Therefore, the simplified form of 1/2(x + 4) + 1/4(4x - 2) is (3/2)x + 1/2.
To simplify 1/2(x + 4) + 1/4(4x - 2), we'll begin by distributing the fractions across the parentheses:
1/2(x + 4) + 1/4(4x - 2) = 1/2 * x + 1/2 * 4 + 1/4 * 4x - 1/4 * 2
= (1/2)x + 2/2 + (1/4)(4x) - (1/4)(2)
= (1/2)x + 1 + (1/4)(4x) - (1/4)(2)
= (1/2)x + 1 + (1/4)(4x) - 1/2
Next, we'll simplify each fractional coefficient:
= (1/2)x + 1 + (4/4)(x) - 1/2
= (1/2)x + 1 + (x) - 1/2
Combining like terms:
= (1/2)x + x + 1 - 1/2
= (1/2 + 2/2)x + 2/2 - 1/2
= (3/2)x + 1/2
Therefore, the simplified form of 1/2(x + 4) + 1/4(4x - 2) is (3/2)x + 1/2.